PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS TERHADAP PENERAPAN GOOD CORPORATE GOVERNANCE BISNIS SYARIAH BUS DI INDONESIA - Eliana Eliana; Nurhayati Nurhayati; Ayumiati Ayumiati (Universitas Pamulang, 2020)
The implementation of bad corporate governance does not only occur in the world's leading companies but in Indonesia also found several similar cases that befell several banks, namely Citibank and Bank Mega, both of these banks are known to violate the implementation of Good Corporate Governance which results in large losses and of course an impact on economic development. This study aims to determine the effect of company size, leverage, and profitability on the implementation of GCGBS in Islamic commercial banks in Indonesia. The sample used was 11 Islamic commercial banks.Regression test results explain that company size and leverage have no significant effect on the implementation of GCGBS in Islamic commercial banks, profitability has a positive and significant effect on the implementation of good corporate governance in Islamic business in Islamic commercial banks in Indonesia.